Focal segmental glomerulosclerosis in a patient with mantle cell lymphoma. (9th September 2015) - Hindocha, Sumeet; Gopaluni, Seerapani; Collins, Graham P; Shenbagaraman, Packiam
Abstract : Mantle cell lymphoma (MCL) is a rare lymphoid neoplasm occurring in about 6% of all non-Hodgkin's lymphomas. Although nephrotic syndrome due to various glomerulopathies is well described in patients with lymphomas, focal segmental glomerulosclerosis (FSGS) with MCL has been reported only once before. We present a second case of FSGS associated with MCL that was resistant to standard treatment of FSGS but resolved when the underlying MCL was treated.